An adaptive proportional-integral-resonant controller for speed ripple suppression of PMSM drive due to current measurement error. (July 2021) - Zhang, Qiaofen; Guo, Haohao; Guo, Chen; Liu, Yancheng; Wang, Dong; Lu, Kaiyuan; Zhang, Zhenrui; Zhuang, Xuzhou; Chen, Dunzhi
Highlights: Design a frequency-adaptive and parameters-robustness PIR controller for PMSM system. Making a tradeoff between stability margin and harmonic suppression capability. Ensuring the stability of the original system not being affected by PIR controller. Improving the steady-state precision without affecting the transient performance. Abstract: An adaptive proportional-integral-resonant (PIR) controller with piecewise phase compensation is proposed to suppress the steady-state speed ripple of permanent magnet synchronous motor (PMSM) drive due to current measurement error. The frequency-varying characteristic of PMSM drive makes the parameters determination of the resonant controller more complicated when considering frequency adaptation. In this paper, after theoretical analysis on the current measurement error, the resonant controller is added in the speed PI loop of the PMSM vector control system, which makes the system more prone to instability. In order to ensure the stability of the system at different speeds, the resonant gain is firstly restricted by root locus method to get a stable system in the full speed range. Then, the resonant gain and the phase angel are further designed to obtain a robust vector margin by Nyquist diagram in different speed ranges. Such piecewise phase compensation method can achieve good stability margin and harmonic suppression ability by making a trade-off between them, avoiding the complicated calculation of the trigonometric functions for compensation in real time. Both steady and transient experiment results indicate that the proposed PIR controller can well restrain the frequency-varying speed ripples caused by current measurement error.